(12y+9x)-(x-y)=

Simple and best practice solution for (12y+9x)-(x-y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12y+9x)-(x-y)= equation:


Simplifying
(12y + 9x) + -1(x + -1y) = 0

Reorder the terms:
(9x + 12y) + -1(x + -1y) = 0

Remove parenthesis around (9x + 12y)
9x + 12y + -1(x + -1y) = 0
9x + 12y + (x * -1 + -1y * -1) = 0
9x + 12y + (-1x + 1y) = 0

Reorder the terms:
9x + -1x + 12y + 1y = 0

Combine like terms: 9x + -1x = 8x
8x + 12y + 1y = 0

Combine like terms: 12y + 1y = 13y
8x + 13y = 0

Solving
8x + 13y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13y' to each side of the equation.
8x + 13y + -13y = 0 + -13y

Combine like terms: 13y + -13y = 0
8x + 0 = 0 + -13y
8x = 0 + -13y
Remove the zero:
8x = -13y

Divide each side by '8'.
x = -1.625y

Simplifying
x = -1.625y

See similar equations:

| -3(5s-6)-18=-3(7s+2)-3 | | 3/4x2=21 | | 5X/6-3/8=7X/4 | | 16x-1024/x2 | | 4(n-25)=9n | | 18000+36000r+18000r^2=0 | | 100-207/8 | | 24.6176=3.14r^2 | | 4x-12=7+7x-4 | | 0.8=5.8/x | | 1.2x+5=3.4 | | 2x^3+3x^2-29x-60=0 | | (2/3)/(3/11) | | 18000+36000r+18000r^2=0 | | 4x=10x-36 | | 6(w-2)-4=-2(-8w+9)-2w | | x=15-4(3+32) | | -14x-67=-11 | | p(-3)=3x^2-5x+7 | | P=4n+32 | | 5(x+1)+4(x+4)=75 | | -7+5=48 | | 4x+15+43=90 | | -0.5-2.7=-1.7 | | 6u+6-2(-4u-1)=2(u-3) | | -12x-10=-11x+16 | | Sin^4(3x/2) | | 6x^2y+8xy+2=0 | | 7(2b+1)-3b=29 | | 4a(a^4)7a=a(4a^3)+20 | | 6x^2y+8xy+2= | | 4x/4=29/8 |

Equations solver categories